Gastronomy as tourist attraction of a destination - Oliveira, Simão (2012)
In the last decades, people's interest about gastronomy has been increasing, being a reflection of this interest, trips motivated by gastronomy. There is, today, no doubt that the gastronomy can be a tourist attraction, however there is still much work to be developed because several regions do not potentiate their gastronomic resources in the best way. The rural space can benefit greatly from the cross between gastronomy and tourism, because these spaces normally retain flavors, ethnographic and authenticity traces that tourists travelling for gastronomy seek. In my presentation, based in 3 case studies in Portugal, i´ll talk about the potential from the gastronomy as a tourist attraction and a way to achieve regional development.